The Legal Protection of Maritime Workers in Light of Jordanian Legislation and International Labor Standards - Al-Araishy, Omar Ahmad (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to clarify the concept of a maritime worker, the meaning of a maritime employment contract and its legal nature, highlight the key rights enjoyed by maritime workers and the mechanisms that contribute to protecting their rights, and evaluate the effectiveness of Jordanian legislation in enhancing the rights of maritime workers and providing a suitable working environment for them, as well as its alignment with international labor standards. Methods: In this study, the researcher followed a descriptive and analytical approach. The descriptive approach involves outlining the legal provisions governing the maritime worker and the maritime employment contract, while the analytical approach focuses on analyzing the legal texts in the Maritime Trade Law and the Labor Law, drawing on legal scholarship and judicial rulings, and comparing them with international labor standards set by the International Labour Organization. Results: The study found several conclusions, including that the maritime employment contract is subject to the provisions of the Labor Law in cases not covered by the Maritime Trade Law. Additionally, the regulation of the maritime employment contract by the Jordanian legislator has created legal issues, including the failure to include the basic elements of a maritime employment contract in the definition of a maritime worker. Conclusions: It is necessary to review the legislation governing the work of maritime workers to align it with international labor standards, especially the Maritime Labour Convention, and with the current Labor Law to keep pace with developments in the maritime transport sector.